Puddles and ponds - Wyler, Rose frey50; Petruccio, Steven Ill. (Julian Messner Englewood cliffs, NJ, 1990)
Describes in simple text and illustrations the plants and animals that live in and around ponds and other small bodies of water. Includes instructions for simple experiments.
Keywords: Pond ecology; Ecology